Blood transfusion practices in a tertiary care hospital in Nepal - Shrestha, Amar Narayan; Aryal, Barun Babu; Poudel, Ayusha; Poudel, Shraddha; Shrestha, Shreya; Adhikari, Anurag; Chhetri, Prakrit (Journal of Pathology of Nepal, 2020)
Background: Blood transfusion is an integral part of patient management. Good transfusion practice guided by standard protocols is considered ideal for optimal use of resources and manpower. Cross-match requests disproportionate to the actual requirement causes overestimation of blood usage and potential wastage. This study aims to determine the crossmatch, transfusion, and utilization rates for blood using transfusion index, and cross-match to transfusion ratio in the various departments of the hospital for the evaluation of transfusion practices. Materials and Methods: A retrospective study was conducted using the records from the hospital blood bank for 12 months to obtain transfusion and cross-match records from various clinical units. Transfusion requests, units cross-matched, and completed transfusions were used to calculate the cross-match to transfusion ratio, and transfusion index for each department. Results: A total of 5156 units of blood were cross-matched for 3437 transfusion requests, out of which 3752 were transfused, giving a mean cross-match to transfusion ratio of 1.37. The non-usage of blood was 27.2% and the transfusion index stood at 1.09. The cross-match to transfusion ratio for the individual clinical units ranged from 1.75 (Surgery) to 1.14 (Medicine). Conclusions: The cross-match to transfusion ratio and transfusion index were within recommended ranges, showing good utilization and low blood wastage. The establishment of a blood ordering protocol via a multidisciplinary approach should be considered to further optimize blood transfusion practices.